Representa????es sociais da revers??o da aposentadoria de servidores p??blicos federais do Poder Executivo - Santos, Val??ria Moreira Neves dos (2018)
The figure of retirement granted in 1821, by Dom Pedro de Alc??ntara, now regulated by the Federal Constitution, has, over time, undergone several transformations, including incorporating compulsory and invalidity. However, it was only in 1990, after the publication of Law number 8.112, that the Retirement Reversal Institute has become a possibility within the legal system governing the federal public service. Public interest in the theme of "aging" is justified by the increase in the number of years lived by individuals in general, without disregarding the fact that the "retirement" status represents a considerable part of the life cycle of the elderly. This has awakened society to look at the factors that can contribute to improving the quality of life at this stage. Many theoretical models have attempted to explain the psychological, physical, and social experiences related to retirement. The "adjustment" to retirement is a process that encompasses physical, cognitive, motivational, emotional, financial and social resources. It is exactly in this process of "adjustment" that this study seeks to understand the significance of what socially represents the institute of the reversion of retirement in the context of the federal public service of the Executive Power, through the social representations of the retirement of these civil servants. Thus, demand also involves the investigation of the perceptive aspects of aging linked to the act of reversing retirement. The idea is based on the construction of a narrative in the context of a semi-structured interview with elderly men and women, aged between 55 and 75 years, who requested a reversal of retirement between 2014 and 2016 in the Governing Bodies of the Federal Executive Branch, located in the Federal District / DF. It is important to note that there is no interest in reversion data referring to the year 2017 due to the fact that the National Congress is already contemplating a Pension Reform, which in a way, reduces the interest for possible reversals, and may mask the research result. This study will focus on the perspective of approach to subjective points of view, with method of data collection focused on structured interviews and as a method of interpretation, procedures of semantic categorization, contemplating the "theme" as the unit of registration or significance in the analysis of content, as proposed by Bardin (2008). The results, systematized in themes, show that the reversal of retirement was not socially indifferent and that its motivation was not essentially motivated by the financial question. The reversion associated with the world of work as habitus and social identity has positive meanings for people such as having contacts, getting out of inactivity, having social utility, valuing oneself, leaving idleness, being productive, financially improving, living, being happy. The repercussions ratified the need to think about projects or actions in the transition to retirement. The study also revealed that this theme in the social representation of the centrality of work as identity, as habitus, as a link, as a financial condition, as utility and productivity shows its complexity and the relation between the common sense imaginary and the practice of this group.